The common iliac artery in the ground squirrel (Citellus citellus) - Blagojević M.; Nešić Ivana; Đelić N.; Jović S.; Đorđević Milena; Savić-Stevanović Vera (Acta Veterinaria, 2013)
The common iliac arteries (a. iliaca communis dextra et a. iliaca communis sinistra) are the terminal branches of the abdominal aorta. The paired external iliac artery (a. iliaca externa dextra et a. iliaca externa sinistra) is a stronger branch of the paired common iliac artery. Before they leave the abdominal cavity and continue as the femoral arteries (a. femoralis dextra et a. femoralis sinistra) each external iliac artery forms the following branches: 1. The internal pudendal artery (a. pudenda interna) which, with its branches, supplies the tensor fasciae latae and quadriceps muscles (a. circumflexa femoris lateralis), cranial region of the urinary bladder, cranial end of the uterine horn in females, the deferent duct and tail of the epididymis in males (a. umbilicalis) the rectum, the external anal sphincter and perineum (a. rectalis caudalis) with blood. 2. The obturator artery (a. obturatoria), which supplies both of the obturator muscles, as well as the proximal end of the adductor muscle. 3. The pudendoepigastric trunk (truncus pudendoepigastricus) is a short vessel, which with its branches (a. pudenda externa, a. epigastrica caudalis et a. urethrogenitalis) supplies the caudal end of the rectus abdominis muscle, tip of the penis, preputium, superficial inguinal lymph nodes, scrotum in males and inguinal mamma in females, transversus and internus abdominis muscles, neck of the urinary bladder, urethra, vagina and vulva in females and accessory glands in males. 4. Paired internal iliac arteries (a. iliaca interna dextra et a. iliaca interna sinistra) are thinner branches than the external iliac arteries. The internal iliac artery with its branches supplies the cranial and caudal parts of the gluteal muscles (a. glutea cranialis et a. glutea caudalis), as well as the muscles of the lateral side of the tail (a. caudalis lateralis). [Projekat Ministarstva nauke Republike Srbije, br. 143018]